Pharmacist-Driven Spirometry Screening to Target High-Risk Patients in a Primary Care Setting - Jangus B. Whitner; Lisa A. Mueller; Alexa Sevin Valentino (SAGE Publishing, 2019)
Objectives: The primary objective of this study is to determine the effect of proactive pharmacist identification of high-risk patients eligible for diagnostic spirometry testing on the percentage of appropriate spirometry referrals ordered and the percentage of spirometry tests completed in those that qualify. Methods: This prospective study compares spirometry referrals ordered and tests completed between an intervention site and control site within a federally qualified health center (FQHC) where pharmacists provide spirometry services. At both sites, all patients who had a primary care provider (PCP) appointment and qualified for spirometry screening on the designated intervention dates during a 12-week period were included in this study. At the intervention site, the pharmacist recommended a spirometry screening to the PCP prior to identified high-risk patients' appointments. At both sites, a chart review was completed to determine if referrals were ordered and tests were completed for patients who qualified. Results: The number of patients eligible for diagnostic spirometry testing at the intervention and control sites was 190 (n = 125 vs n = 65, respectively). Among eligible patients, the percentage of referrals ordered was significantly higher at the intervention site (47.2% vs 7.7%, P < .001). Among patients who qualified, completion of spirometry testing was significantly higher in the intervention site (23.2% vs 3.1%, P < .001). Conclusion: Results of this study suggest that pharmacists proactively identifying high-risk patients for spirometry screenings within an FQHC increases appropriate referrals ordered by PCPs and tests completed by high-risk patients. Pharmacists in the primary care setting can aid the PCP in the management of chronic obstructive pulmonary disease through significantly increased spirometry referrals and therapeutic clinical assessments and recommendations. They also can provide face-to-face motivational counseling for smoking cessation, inhaler education, and vaccine recommendations. This population health approach to spirometry testing represents an emerging role for pharmacists and could be adopted in other primary care settings.